(untitled) (ModaPalavra e-periódico, 2024)
In recent years, especially in Brazil, we have advanced in discussions about sustainability in the fashion chain. In order to contribute to studies in the area, this research aims to discuss teaching for sustainability in undergraduate courses in Fashion Design. The research started with a bibliographic survey about publications on fashion teaching in journals in the last ten years, which culm in the creation of a questionnaire, which was applied to twelve teachers. As a result, it is expected to contribute to the education of fashion professionals for a context more aligned with sustainable development.